Molecular Markers Reveal Epidemiological Patterns and Evolutionary Histories of the Human Pathogenic Cryptococcus - Hong, Nan; Chen, Min; Xu, Jianping (Frontiers in Cellular and Infection Microbiology, 2021)
The human pathogenic Cryptococcus species are the main agents of fungal meningitis in humans and the causes of other diseases collectively called cryptococcosis. There are at least eight evolutionary divergent lineages among these agents, with different lineages showing different geographic and/or ecological distributions. In this review, we describe the main strain typing methods that have been used to analyze the human pathogenic Cryptococcus and discuss how molecular markers derived from the various strain typing methods have impacted our understanding of not only cryptococcal epidemiology but also its evolutionary histories. These methods include serotyping, multilocus enzyme electrophoresis, electrophoretic karyotyping, random amplified polymorphic DNA, restriction fragment length polymorphism, PCR-fingerprinting, amplified fragment length polymorphism, multilocus microsatellite typing, single locus and multilocus sequence typing, matrix-assisted laser desorption/ionization time of flight mass spectrometry, and whole genome sequencing. The major findings and the advantages and disadvantages of each method are discussed. Together, while controversies remain, these strain typing methods have helped reveal (i) the broad phylogenetic pattern among these agents, (ii) the centers of origins for several lineages and their dispersal patterns, (iii) the distributions of genetic variation among geographic regions and ecological niches, (iv) recent hybridization among several lineages, and (v) specific mutations during infections within individual patients. However, significant challenges remain. Multilocus sequence typing and whole genome sequencing are emerging as the gold standards for continued strain typing and epidemiological investigations of cryptococcosis.